OS 33-08 OBSTRUCTIVE SLEEP APNEA PROMOTES CARDIOVASCULAR RISK IN HYPERTENSIVE POPULATIONS: A CROSS-SECTIONAL STUDY. (September 2016) - Cai, Anping; Wang, Ling; Zhou, Yingling; Chen, Jiyan; Feng, Yingqing; Zhong, Qi
Abstract : Objective: Current study sought to evaluate the effects of obstructive sleep apnea (OSA) plus hypertension (HTN) on prevalent cardiovascular diseases (CVD). Design and Method: This was a cross-sectional study and a total of 1889 subjects were enrolled. The apnea-hypopnea index (AHI) was measured by polysomnography and OSA degree was classified as mild (AHI 5–14.9) and moderate-severe (AHI ≥ 15), and AHI < 5 was considered no-OSA. Mean and lowest oxyhemoglobin saturation (SaO2 ) was detected by pulse oximetry. Between-group differences were assessed and logistic regression analysis was used to analyze the effects of OSA plus HTN on prevalent CVD which included coronary heart disease, ischemic stroke, aortic dissection and aneurysm. Results: Compared to normotensive subjects, hypertensive subjects were older and had higher body mass index, neck girth, waist-hip ratio, blood pressure, AHI, and low density lipoprotein. Conversely, mean and lowest SaO2 levels were significantly lower. Similar trends were observed in moderate-severe-OSA subjects compared to subjects with mild-OSA or no-OSA. Logistic regression analysis showed that in unadjusted model, compared to subjects with no-OSA and no-HTN (reference group), subjects with either OSA or HTN had higher CVD prevalence, with most prominent in HTN plus moderate-severe-OSA group (OR: 2.638 and 95 % CI: 1.942–3.583). In normotensive subjects, after adjusting for covariates, the effects of OSA (regardless of severity) on CVD were attenuated to nonsignificant. In hypertensive subjects, however, the effects of OSA on CVD remained significant but were reduced, with HTN plus moderate-severe-OSA was attenuated most prominently (OR: 1.836 and 95 % CI: 1.266–2.663). Further adjusting for mean and lowest SaO2, the effects of OSA remained significant and were promoted in subjects with HTN plus mild-OSA and HTN plus no-OSA, but not in subjects with HTN plus moderate-severe OSA. Conclusions: OSA promotes CV risk in hypertensive subjects, which is independent of mean and lowest SaO2 .